Характеристика принципів діяльності Державного бюро розслідувань України - Лісойван, Я. М.; Lisoivan, Ya. M. (Європейські перспективи. - 2023. - № 2. – С. 53-59, 2023)
Надано правовий аналіз принципів діяльності Державного бюро розслідувань, визначено їх особливості та виявлено проблемні аспекти реалізації у практичній діяльності ДБР. Наголошено, що принципи діяльності Державного бюро розслідувань представляють собою взаємопов’язану систему керівних ідей, яка є непорушним фундаментом для ефективного функціонування вказаного правоохоронного органу та плацдармом для успішної реалізації завдань, що поклали на нього суспільство та держава. У той же час нормативно – правові засади діяльності Державного бюро розслідувань та їх неухильне дотримання покликані забезпечити якісне виконання вказаних викликів на правовому полі.

The article examines the legal essence of the principles of activity of law enforcement agencies of Ukraine. It is noted that the principles of law enforcement agencies represent a monolithic, inviolable structure, the foundation of which is a set of inseparable elements that correlate with each other in terms of goals, the vector of which is directed to the performance of common tasks and functions. The principles of the State Bureau of Investigations are built in close connection with the general system of principles of the functioning of law enforcement agencies in general. It is emphasized that according to the current legislation of Ukraine, the State Bureau of Investigation was created on the basis of:- 1) the supremacy of law, according to which a person, his life and health, honor and dignity, inviolability and security are recognized as the highest social value, and human rights and freedoms and their guarantees determine the content and direction of the state’s activities;- 2) legality; 3) justice; 4) impartiality;- 5) independence and personal responsibility of each employee of the State Bureau of Investigation; 6) openness and transparency of the activities of the State Bureau of Investigations for society and democratic civil control, accountability and control over the state bodies defi ned by law; 7) political neutrality and non-partisanship; 8) unity of leadership in the implementation of the powers of the State Bureau of Investigation. The principle of single leadership does not negate the principle of procedural independence of the investigative body of the State Bureau of Investigation. It was emphasized that the principles of the State Bureau of Investigation represent an interconnected system of guiding ideas, which is an unbreakable foundation for the effective functioning of the specifi ed law enforcement agency and a springboard for the successful implementation of the tasks assigned to it by society and the state. At the same time, the regulatory and legal principles of the State Bureau of Investigation and their strict observance are designed to ensure the quality of the specifi ed challenges in the legal fi eld.

Представлен правовой анализ принципов деятельности Государственного бюро расследований, определены их особенности и выявлены проблемные аспекты реализации в практической деятельности ГБР. Отмечено, что принципы деятельности Государственного бюро расследований представляют собой взаимосвязанную систему руководящих идей, которая является незыблемым фундаментом для эффективного функционирования указанного правоохранительного органа и плацдармом для успешной реализации задач, возложенных на него обществом и государством. В то же время нормативно – правовые основы деятельности Государственного бюро расследований и их неукоснительное соблюдение призваны обеспечить качественное выполнение указанных вызовов на правовом поле.
Principles of activity of the State Bureau of Investigation
Лісойван, Я. М. Характеристика принципів діяльності Державного бюро розслідувань України / Лісойван Ярослав Миколайович // Європейські перспективи. - 2023. - № 2. – С. 53-59. - DOI: 10.32782/EP.2023.2.9.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Державне бюро розслідувань України; State Bureau of Investigation of Ukraine; Государственное бюро расследований Украины; правоохоронні органи; law enforcement agencies; правоохранительные органы; принципи; principles; принципы; законність; legality; законность; справедливість; justice; справедливость; незалежність; independence; независимость